Reliability of the Athletic Shoulder test in asymptomatic and symptomatic overhead racquet athletes - Schellekens, M.; Struyf, F.; Verheyen, N.; Pittoors, J.; Cavaggion, C. (Physical Therapy in Sport, 2025)
Objectives Assessing intra- and inter-rater reliability of the Athletic Shoulder (ASH) test using a force plate in asymptomatic and symptomatic overhead racquet athletes.